Human factors of successful teams and their impact on emloyees - Hebeny-Fuchs, Orsolya; Fehérné Kiss, Marianna; Mikola, Gergely; Zsolt, Kőműves (Studia Mundi – Economica, 2024)
Our study intends to approach this question from the human side. Human resource play a central role in every organization. The reason for this is complex: on the one hand, companies recognized that people have special qualities (independent will, attitude, skills, etc.), and on the other hand, they cannot be replaced, or can be replaced only to a limited extent. All of this is reinforced by the lack of adequate human resources. In addition to the personality and individual perfomance of team members and managers, these employees must also be able to work together as a group. In our study, we would like to answer the following questions related to effective groups: What influences effective and efficient work? What characterizes a successful team and its leader, as well as a subordinate working in a successful team? We hope that our readers will receive answers to these questions that can be used in practice. Hypothesis: In our research, we examined whether a team – which was effective based on the the results of the performance evaluation given by the respondents’ employers – meets the five criteria for successful groups described by Lencioni? Whether the leaders of these effective groups have Sinek’s five basic leadership skills? Whether the team members of these groups have the three qualities included in the "Ideal Team Player Model" formulated by Lencioni? And whether they are more committed? Methodology: In the framework of primary quantitative research, we reached 140 people with our questionnaire. Results: Summarizing the obtained results, the four hypotheses proved to be basically correct, showing moderately strong or weak relationship. Conclusion: If organizations want to achieve greater success or aim to retain "ideal" employees, fine-tuning is necessary in the areas and processes that show weaker results. This can be achieved by changing the company’s approach and/or management mindset and behavior.